Mouthguard use, hygiene, and maintenance practices among combat and team sports athletes: A comparative study - Didem Özkal Eminoğlu; Kamber Kaşali; Cebrail Gençoğlu; Süleyman Ulupinar; Serhat Özbay; Buket Şeran; Ayşegül Türksoy; Fatih Kiyici (PLoS ONE, 2025)
This study aimed to investigate the attitudes of combat and team sports athletes towards the use, storage, and hygiene conditions of mouthguards, with the goal of understanding disparities in usage and maintenance practices and their implications for oral health. A cross-sectional study was conducted involving 394 athletes (316 combat athletes and 78 team athletes). Participants completed a 28-question survey assessing their knowledge, attitudes, and practices regarding mouthguard use, hygiene, and maintenance. The survey included questions on demographic data, mouthguard usage habits, cleaning methods, and storage practices. Combat sports athletes exhibited significantly higher rates of mouthguard use (100%) compared to team sports athletes (29.5%) (chi square [χ2] = 258.971, p<0.001). Significant differences were also found in cleaning (χ2 = 252.195, p<0.001) and storage practices (χ2 = 14.195, p = 0.002), with combat athletes demonstrating better adherence to recommended guidelines. Common complaints about mouthguards included difficulties with speaking (χ2 = 7.792, p = 0.005) and breathing (χ2 = 11.431, p = 0.001), with combat athletes reporting fewer issues. The study highlights the need for increased awareness and education on mouthguard use among team sports athletes. Dentists and coaches play a crucial role in promoting proper mouthguard use, hygiene, and maintenance to prevent sports-related dental injuries. Emphasis should be placed on the benefits of custom-made mouthguards for improved comfort and protection.